Microbial lipid production from rice straw hydrolysates and recycled pretreated glycerol. (September 2020) - Tang, Song; Dong, Qian; Fang, Zhen; Cong, Wen-jie; Zhang, Huan
Graphical abstract: Highlights: Lipid fermentation of glucose was optimized by response surface methodology. Glycerol-FeCl3 pretreated straw with 96% cellulose recovery & 72% lignin removal. 74.3% glucose yield was achieved at 20% solid loading and 3 FPU/g for 72 h. High total lipid (8.8 g/L) with 0.17 g/g yield achieved from straw hydrolysates. Recycled pretreated glycerol was fermented to lipid with 0.16 g/g lipid yield. Abstract: Microbial lipids were produced by both rice straw hydrolysates and recycled pretreated glycerol. First, lipid fermentation of glucose via Cryptococcus curvatus was optimized by response surface methodology. Variables were selected by Plackett–Burman design, and optimized by central composite design, achieving 4.9 g/L total lipid and 0.16 g/g lipid yield, and increased further as glucose increased from 30 to 50 g/L. Secondly, after pretreatment, 72% lignin of rice straw was removed with glucose yield increased by 2.4 times to 74% at 20% substrate and 3 FPU/g. Subsequently, its hydrolysates produced high total lipid (8.8 g/L) and lipid yield (0.17 g/g). Finally, recycled glycerol reached the maximum total lipid of 7.2 g/L and high lipid yield of 0.16 g/g. Based on the calculation, 2.9 g total lipid would be produced from 1 g rice straw and the recycled glycerol, with a similar composition to soybean oil.